Asymptotic Properties of Parameter Estimators in Fractional Vasicek Model - Lohvinenko, Stanislav; Ralchenko, Kostiantyn; Zhuchenko, Olga (Lithuanian Journal of Statistics, 2016)
We consider the fractional Vasicek model of the form dXt = (α-βXt)dt + γdBHt, driven by fractional Brownian motion BH with Hurst parameter H ∈ (0,1). We construct three estimators for an unknown parameter θ=(α,β) and prove their strong consistency.